Medieval theoretical principles of medicine in Ibn Sīnā’s al-Qānūn fī al-Ṭibb and al-Dhahabī’s al-Ṭibb al-Nabawī - Muhammad Yusoff, Muhammad Fawwaz; Ab Razak, Nur Izah (University of Malaya, 2020)
The Galenic account of medicine by Ibn Sīnā (d. 427AH/1037CE) was remarkably significant for natural philosophy and religious thought in the medieval Islamic world. Just as one might split philosophy in the Islamic world into eras before and after Avicenna, so one could periodise medical history into the time before and after Ibn Sīnā’s glorious al-Qānūn fī al-Ṭibb (Canon of Medicine). This article compares the medical theory in al-Qānūn fī al-Ṭibb and al-Dhahabī’s (d. 748/1348) al-Ṭibb al-Nabawī to determine if the medieval al-Ṭibb al-Nabawī genre was influenced by the post-Avicennian tradition. To assess this theoretical impact on the writing in the prophetic medicine genre, the article first analyses the introductory part of both writings, as well as the subsequent developments in al-Ṭibb al-Nabawī writings. This will form a comparative view of the medieval anatomical and philosophical positions. Given that traditional prophetic medicine is the focus of the al-Ṭibb al-Nabawī genre, the article turns to the question of medical theory, did al-Dhahabī really observe this topic? What role does medical ḥadīth play in determining how Muslims should approach classical theories of medicine? By comparing these two works, one can see that al-Dhahabī’s al-Ṭibb al-Nabawī developed in interaction with and extension of the al-Qānūn fī al-Ṭibb, as well as an attempt to bring forth a new form of medicine, that would integrate Ibn Sīnā’s medical theory with Prophetic ḥadīth.